Hadis-hadis tentang Pengobatan Herbal: Studi Takhrij dan Syarah Hadis dengan Tinjauan Kesehatan - Muhammad Luthfi Bakti Islami (Jurnal Penelitian Ilmu Ushuluddin, 2022)
This study aims to discuss the hadiths regarding herbal medicine with a health review. This study applies a qualitative type through literature study using the takhrij and syarah hadith methods. The results and discussion of this study include an overview of herbal medicine, editorials of hadith on herbal medicine, understanding of hadith regarding herbal medicine, and the content and benefits of herbal medicine for health. This study concludes that the herbal treatment recommended by Rasulullah SAW. proven in modern medicine has many health benefits. This can strengthen the hadith of the Prophet Muhammad. where the hadith appeared long before the advancement of medical science and technology.